Causas emocionales y nutricionales relacionadas a las enfermedades Gastrointestinales en estudiantes de la Facultad Ciencias de la Salud – Universidad Nacional de San Martín Tarapoto, Octubre 2015 – Marzo 2016 - Marín Cárdenas, Susan Ibeth (2016)
The following study "Emotional and nutritional causes related to Gastrointestinal Diseases in students of the Faculty of Health Sciences - National University of San Martin Tarapoto, October 2015 - March 2016", following a quantitative, descriptive, transversal, correlational study with prospective data collection , Whose population was 41 students, being the sample 41 students, the method used was the survey and the instrument the questionnaire. The results were: the students are single 70.7% and come from the urban area 75.6%. Among the emotional causes we have: 39.0% feel joy or laughter frequently. 34.1% feel anger, anger or anger during their studies. 31.7% are frequently distressed. 43.9% demand a high concentration. 68.3% are afflicted by personal situations that affect their studies. 24.4% are often fearful. 17.1% have resentment toward something or someone around them. 12.2% receive much criticism from their teachers, peers, relatives in their studies. Among the nutritional causes we have: 85.4% frequently consume some foods that are alkalizing. 85.4% frequently consume some foods that are acidifying. 43.9%, frequently consume some foods that are neutral. 29.3% consume their food on time. In conclusion: The emotional cause - affliction by study or by personal aspects is significantly related to gastrointestinal disease at a level of 5%, p_value is 0.001